Linking Emissions Trading Schemes in the Presence of Research and Develoment Spillovers - Daniel Nachtigall (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
I analyze the role of research and development (R&D) spillovers on the incentives to link emissions trading schemes (ETSs) under different timings with respect to the determination of the emissions reduction target (ERT) and to the linking decision. When countries decide upon linking their ETSs prior to setting their ERTs, the permit importing country may not consent to link in the absence of R&D spillovers. The reason is that the other country strategically decreases its ERT to increase its revenues from permit trading, thereby increasing the costs for the permit importing country. However, in the presence of R&D spillovers, the permit importing country benefits from higher R&D spillovers and from lower environmental damage under linking relative to autarky and is therefore willing to link. When countries determine their ERTs prior to the linking decision, the role of R&D spillovers on the linking decision reverses. In the absence of R&D spillovers, both countries unambiguously are willing to link their ETSs due to the efficiency gains from trade. However, if R&D spillovers are relevant, the permit exporting country may be worse off under linking because its R&D spillovers deteriorate due to lower abatement effort by the other country. Hence, there is a trade-off between the efficiency gains from trade and the reduced R&D spillovers, causing the permit exporting country to reject linking if the spillover effect is sufficiently large.
Keywords: H41; Q54; Q56; 330